2020
DOI: 10.3390/cells9020315
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Comparison of Stem Cells Secretome and Levodopa Application in a 6-Hydroxydopamine Rat Model of Parkinson’s Disease

Abstract: Parkinson’s Disease (PD) is characterized by the massive loss of dopaminergic neurons, leading to the appearance of several motor impairments. Current pharmacological treatments, such as the use of levodopa, are yet unable to cure the disease. Therefore, there is a need for novel strategies, particularly those that can combine in an integrated manner neuroprotection and neuroregeneration properties. In vitro and in vivo models have recently revealed that the secretome of mesenchymal stem cells (MSCs) holds a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 91 publications
0
16
0
Order By: Relevance
“…Contrarily to lesions in the SNpc and striatum, MFB lesions have the advantage of mimicking the late stage of PD [27]. Moreover, it avoids direct mechanical damage of the SNpc and striatum, allowing further screening studies, such as the injection of cell grafts, neuroprotective molecules, as wells as the cellular secretome into these brain regions [13,14,16,28].…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily to lesions in the SNpc and striatum, MFB lesions have the advantage of mimicking the late stage of PD [27]. Moreover, it avoids direct mechanical damage of the SNpc and striatum, allowing further screening studies, such as the injection of cell grafts, neuroprotective molecules, as wells as the cellular secretome into these brain regions [13,14,16,28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been suggested that the antioxidant effect, which is elicited by MSC-derived secretome, could bring about by Sirt3 delivery, leading to substantial neuroprotective influences in vivo [ 156 ]. Other reports have also shown that desired effects induced by MSC-derived exosome therapy were largely mediated by various biologic molecules in MSC-derived secretome, including stromal cell-derived factor-1 (SDF-1 or CXCL12), growth factors (BDNF, VEGF and GDNF), MMP2, heat shock protein 27 (HSP27), and semaphorin 7a (sema7a) [ 157 ].…”
Section: Preclinical Studies Based On Msc-derived Exosome Therapy In ...mentioning
confidence: 99%
“…Stem cell-derived secretome represents one promising therapeutic strategy. Teixeira et al found that BM-MSCs secretome resulted in a significant amelioration in the animal behavior in a Parkinson’s Disease rat model [ 30 ]. EVs are membrane-bound cellular products (30–1000 nm) that contain various classes of nucleic acids as well as soluble and transmembrane proteins.…”
Section: Stem Cell-based Therapymentioning
confidence: 99%
“…This Special Issue includes both research [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] and reviews articles [ 10 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] which cover wide ranges of stem cell research: adult stem cells, cancer stem cells, pluripotent stem cells, and complex 3D organoid/cell aggregate models [ 26 , 27 , 33 ], with the focuses on stem cell biology/technology [ 10 , 23 , 24 , 25 , 26 , 31 , 32 , 34 ], and stem cell-based disease modeling [ 10 , 27 , 29 , 31 , 33 , 38 , 43 ] and cell therapy [ 24 , 28 , 30 , 32 , 35 , 36 , 37 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation